Evaluate the Organic Farming in Terms of Productivity in India: A Case Study of Andhra Pradesh - Dr.T.Chennakesavulu (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2019)
Statement of Problem Organic farming is one among the many approaches found to fulfill the objectives of property agriculture. Most of the techniques utilized in organic farming like inter-cropping, mulching and integration of crops and placental aren't alien to agriculture systems together with the standard agricultural practices. However, organic farming relies on numerous laws and certification programmes, that compel the employment of just about all artificial inputs and also the central theme of this methodology is that the health of soil. The adverse effects of contemporary agricultural practices on the farm and additionally on the health of living beings and therefore on the setting has been well documented everywhere the globe. Application of technology, significantly U.S.A. either utilization the employment of chemical fertilizers and pesticides all around us has persuaded folks to assume aloud. As a results of international environmental condition changes, their negative effects on the setting area unit manifested through erosion, water shortages, salination, soil contamination, genetic erosion, Organic farming is one among the wide used strategies, that is believed because the best different to avoid the sick effects of chemical farming. It additionally has way more blessings over the standard and alternative fashionable agricultural practices that area unit obtainable these days.